Attitudes Toward a Code of Ethics: a Comparison between Academic and Non-Academic Staff - Putranta, Martinus Parnawa (Media Ekonomi dan Manajemen, 2020)
The frequent media reports on the unethical conduct of business and non-business practitioners has made the roles of universities in equipping organisation leaders with ethics are in question. They are required to foster a better learning environment that enables prospective leaders to enhance their moral sensitivity and appreciate the importance of ethics in their personal and professional life. Academic and non-academic staff of the institutions are in the front line of providing ethical role model to the students. Considering these influential roles an examination of the ethical attitudes of the staff is a good start. A code of ethics has been considered as a symbol of an organisation to preserve and promote ethical concerns. Therefore, ascertainment his research was part of a wider study on ethics in denominational higher education institutions in several cities in Java, Indonesia. In particular, it addressed the attitudes of employees of the institutions’ staff toward their institutional codes of ethics. Initially, this research was going to include employees from those institutions. However, at the time the research was carried out, only one of the institutions has adopted and published a code of ethics. Due to this fact, the scope of the research was then confined into a single institution. The purposes of the article were two-fold. The first was to asses the attitudes of the staff in the institution toward their codes of ethics.  The second was to ascertain whether differences existed between academic and non-academic staff regarding these attitudes.  A cross-sectional survey was employed as the primary method to collect the data. The fieldwork comprised the distribution of a self-administered questionnaire to potential respondents through direct contact.  A purposive sampling was used to identify and invite respondent participation. A total of 200 questionnaires were distributed of which 103 were usable, representing the overall response rate of 50 %. The findings of the research are discussed. A wide range of managerial and scholarly implications are outlined.